The US bioeconomy at the intersection of technology, policy, and education. (13th October 2021) - Pascoli, Danielle U; Aui, Alvina; Frank, Jenny; Therasme, Obste; Dixon, Kerry; Gustafson, Rick; Kelly, Brendan; Volk, Timothy A; Wright, Mark M
Abstract: The bioeconomy is a complex, multivariate, and interdisciplinary system that requires a comprehensive assessment of its independent parts if it is to be understood fully. Hence, this article presents a holistic perspective of industry, public policy, and education aspects of the US bioeconomy. It is premised on the idea that a successful bioeconomy industry relies on the balanced development of all stages of the supply chain. For this balance to be struck, a strong interdisciplinary workforce must find novel solutions to multifaceted problems across the entirety of the supply chain. These solutions require innovative technologies that can improve the climate benefit of bioproducts, decrease their production costs, and make them more economically competitive. Increasing consumer education and awareness about the bioeconomy goes hand in hand with the development of a robust market for bioproducts. To guide these interdependent efforts, public policies must encourage demand, support competitive markets, promote the entry of renewable options, and stimulate growth by reducing financial barriers. We contend that a combination of policies is likely to be more effective than any singular policy on its own. Supporting the bioeconomy also entails attending to an existing lack of public awareness as well as workforce‐ready professionals. To address these gaps, the USA must increase the intensity and intentionality of its efforts to educate students about the bioeconomy, particularly at the K‐12 level. Furthermore, these efforts should encompass both formal and informal learning contexts in order to meet the workforce challenges facing the bioeconomy now and in the future. © 2021 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Industrial Chemistry and John Wiley & Sons Ltd.